Laboratory evaluation of influence of quality treating of root canals from calcium hydroxide on adhesion of root sealers (LLC "Endo Press", 2020)
Results of work on definition of solvent of the Metapex, evaluation of quality treating of root canals are presented in this article after temporary sealing by calcium hydroxide. Are described results of carrying out radiological and scanning electronic microscopy researches. Also presented results on determination of adhesive durability of two types of root sealers. The assessment of influence of quality of treating root canals from preparations of calcium hydroxide on adhesion of sealers is given. The combination of medical ultrasonic passive irrigation with irrigation works best when you remove from the surface of root canal preparations of calcium hydroxide.